Between Scientific Indicators and Regulatory Choices: Science and Law in the Nature Restoration Regulation for Agroecosystems (BioLaw Journal - Rivista di BioDiritto, 2026)
This contribution examines the relationship between science and law in the European Union’s agri-food and environmental policies through the case of Regulation (EU) 2024/1991 on nature restoration. Drawing on a qualitative analysis of the Regulation’s documents and annexes, it reconstructs how scientific evidence is selected and translated into legally binding targets and indicators, highlighting epistemic tensions and simplifications. The assessment of the consultation process and subsequent negotiations reveals existing conflicts between epistemic and democratic legitimacy. The article ultimately interprets the Regulation as a device of institutional co-production between science and law, with implications for the implementation of national restoration plans.
Keywords: nature restoration; environmental law; science and policy; scientific advice; epistemic communities participation